Reliability Model of the Fly-By-Wire System Based on Stochastic Petri Net - Zhong Lu; Zhiwen Zhang; Lu Zhuang; Jia Zhou (International Journal of Aerospace Engineering)
The fly-by-wire system plays an important role in modern civil aircraft. As a typical safety-critical system, its reliability will affect the safety of aircraft significantly. In the paper, stochastic Petri nets are applied in the reliability modeling and analysis for the fly-by-wire system to represent its dynamic (time-dependent) failure behaviors. Stochastic Petri net-based reliability models are established for all kinds of architectures including series, parallel, m-out-of-n, warm standby, cold standby, and load-sharing architectures, which are commonly used in the fly-by-wire system. A Monte Carlo simulation method is proposed for the stochastic Petri net-based reliability models to generate system lifetime samples, and the system reliability parameters can be calculated in terms of the lifetime samples. Finally, a fly-by-wire system is used as a case study to illustrate the application and effectiveness of our proposed approaches. The results show that the error of the reliability value in a flight duration obtained by our Monte Carlo simulation method is less than 1×10−4 compared with the analytical equation.